2015
DOI: 10.1186/s12953-014-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis of differential proteins in respond to doxorubicin resistance in myelogenous leukemia cell lines

Abstract: BackgroundChemoresistance remains a significant challenge in chronic myelogenous leukemia (CML) management, which is one of the most critical prognostic factors. Elucidation the molecular mechanisms underlying the resistance to chemoresistance may lead to better clinical outcomes.ResultsIn order to identify potential protein targets involved in the drug-resistant phenotype of leukemia, especially the chronic myelogenous leukemia (CML), we used a high-resolution “ultra-zoom” 2DE-based proteomics approach to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…Indeed, several studies in different cancer models have demonstrated an efficient suppression of MDR by glycolytic inhibitors823244445. Moreover, during the course of this work another study has suggested the possibility of an accelerated process of glycolysis in MDR cells to increase their energy supply46. To our knowledge, a comparison between MDR and drug-sensitive cells in terms of metabolic energy supply, using different modulators of glycolysis and OXPHOS, has never been performed.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, several studies in different cancer models have demonstrated an efficient suppression of MDR by glycolytic inhibitors823244445. Moreover, during the course of this work another study has suggested the possibility of an accelerated process of glycolysis in MDR cells to increase their energy supply46. To our knowledge, a comparison between MDR and drug-sensitive cells in terms of metabolic energy supply, using different modulators of glycolysis and OXPHOS, has never been performed.…”
Section: Discussionmentioning
confidence: 84%
“…Salivation plays an important role in food consumption and digestion in rodents [37], and have roles in host defense [38]. Thus, salivary gland impairment may potentially impact food intake, body weight and some innate defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were loaded onto an IPG strips with linear PH gradient 4–7 and 24 cm length (GE Healthcare, Uppsala, Sweden). After hydrated, the strips were performed isoelectric focusing (IEF) and SDS-PAGE gels electrophoresis to separate proteins as described48.…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular localization was predicted using CELLO V.2.5 (http://cello.life.nctu.edu.tw). Identified proteins were further analyzed using the STRING V10.0 database (http://string-db.org/) for PPI network analysis, to statistically determine the functions and pathways most strongly associated with the protein list48. KEGG (http://www.genome.jp/kegg/pathway) pathway analysis was performed to determine their molecular interaction and reaction networks52.…”
Section: Methodsmentioning
confidence: 99%